(untitled) (Global Journal of Computer Science and Technology, 2011)
In recent past years, Internet and Mobile is widely used for communication. Multimedia messaging (MMS) and Short Service Messaging (SMS) are the popular services provided by the telecommunication companies. In MMS we can easily send picture with text message. In SMS we can send text only. These techniques make the communication so fast. As well as the communication became easy attention toward information security increased. Data Security is the main concern for research. Mostly used techniques for secure communication are Cryptography and Steganography. There are so many techniques for steganography and cryptography. Mostly used techniques are image steganography and there are so many algorithms for this. For the cryptography mainly AES techniques is being used. In this paper we are presenting a technique using cryptography and steganography for securing information over mobile in MMS. It is very common practice to hide data in LSB of pixel. Spatial and frequency domains are generally used for image processing. Spatial domain have so many computations comparatively frequency domain. There different transform techniques are used for transformation e.g. DCT, FFT and wavelets. Here we are using Discrete Cosine transform (DCT) for image steganography and tiny encryption algorithm for cryptography. Tiny encryption algorithm (TEA) is block cipher algorithm.It is simple and fast but best for mobile application.